(untitled) (Indian Journal of Animal Production and Management, 2025)
Magnesium is an essential mineral that plays a central role in numerous enzymatic reactions, neuromuscular function, and energy metabolism. Deficiency of magnesium in ruminants is often underdiagnosed due to the absence of pathognomonic signs, yet it may substantially impair productivity and health. In the Basrah region of southern Iraq, buffaloes represent a vital livestock resource, and subclinical nutritional imbalances may negatively affect their performance. The present investigation was managed to investigate the epidemiological aspects, biochemical alterations, and clinical manifestations related to magnesium deficiency in buffaloes located north of Basrah. A total of 112 buffaloes were examined through clinical evaluation and laboratory analysis. Serum concentrations of magnesium, calcium, phosphorus, sodium, potassium, alkaline phosphatase, total protein, and albumin were measured. Environmental parameters, containing ambient temperature, humidity, and wind speed, were also recorded to evaluate their potential contribution to deficiency risk. Results demonstrated that affected buffaloes exhibited markedly lower serum magnesium concentrations (0.52 ± 0.01 mmol/L) compared with healthy controls (1.03 ± 0.02 mmol/L; p < 0.05). Clinically, deficient animals presented with loss of appetite, restlessness, progressive emaciation, teeth grinding, muscular tremors, and generalized weakness. Biochemically, magnesium deficiency was strongly related to reduced serum calcium and sodium levels, while potassium was meaningfully elevated. Seasonal variations also influenced magnesium status, with the lowest mean concentrations recorded through December (0.44 ± 0.056 mmol/L), coinciding with adverse climatic conditions. These results propose that nutritional imbalances, compounded by environmental stressors, may predispose buffaloes in Basrah to hypomagnesemia. In conclusion, magnesium deficiency represents an underrecognized metabolic disorder in buffaloes raised under the ecological conditions of southern Iraq. Regular monitoring of mineral status, along with improved nutritional management strategies, is recommended to reduce the incidence of deficiency and enhance overall buffalo productivity.